'Selling the monster' or the relevance of cultural-cognitive conditions in creating demand for innovation: the case of COVID-19 vaccines and beyond. (19th September 2022) - Reale, Filippo
Starting from the current, problematic inertia in citizens' demand for coronavirus vaccinations, the article argues that public demand for innovations crucially depends on consumers' ability to cultural-cognitively process the degree of novelty that the innovation brings about. This is not only of major importance for entrepreneurs who aim to commercialise innovations or otherwise create markets and demand, but as importantly, it concerns innovation and industrial policy who have a responsibility to establish and maintain reliable demand structures. Lastly, it strongly concerns contemporary 'mission-oriented' or transformative innovation policy, since 'grand challenges' can be addressed, and transitions performed only if the technological dynamics involved are accepted on a wide scale. The proposition is that, given the cultural-cognitive origins and the emotive form of certain impediments to demand, rational incentives are largely ineffective remedies for them. Instead, in the short run, social structures are necessary by which to comfort and 'solace' potential consumers.